Internalization of Social Values ​​through Begawe Tradition to Improve Early Childhood Social Skills in the Sasak Tribe - Ahmad Sanusi; Buana Sari (PAUDIA : Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2020)
AbstractSocial skills are social skills possessed b an individual or individual to be able to interact with the surrounding environment. Social skills should be developed as early as possible, because in this early childhood individuals have begun to learn to socialize anda interact with other individuals. Development of social skills in early childhood can be done by instilling social values contained in the tradition of begawe in the sasak trible. Begawe tradition is a joint dining event or party by the sasak tribal community conducted down and down. The research approach used in this article is a qualitative descriftive approach with data collection methods using ovservation, interviews and documentation. This research aims to express the values contained in the begawe tradition in the sasak tribe. The social values that can be channeled to early childhood based on the result of research are cooperation, adaptive behavior, carring attitude, friendship, and compassion.Key words: Social skills, Early Chilhdood, Begawe tradition.